Moments of Insight in Problem‐Solving Relate to Bodily Arousal. (27th May 2021) - Nam, Beth; Paromita, Projna; Chu, Sharon Lynn; Chaspari, Theodora; Woltering, Steven
Abstract: Problem‐solving involves both cognitive and physiological changes. Since most prior work has focused on examining the cognitive side of problem‐solving, there is more to explore on the physiological side, including skin conductance. The present study examined skin conductance reactivity (SCR) to the moment participants solved three different types of problems: (a) straightforward (basic), (b) analytic processing (analytic questions), and (c) a sudden insight (riddles). The authors predict different responses in SCR between basic, analytic, and riddle conditions, and the level of difficulty in riddles. Moreover, the authors predict that a faster and correct response is related to larger physiological arousal. Thirty‐one participants were confronted with problems that were best solved using either sudden insight (riddles) or analytic thinking, as well as a control condition with basic questions. Participants showed the largest SCR amplitudes to the insight condition versus the basic control condition. Furthermore, hard insight problems had greater SCR amplitudes than easy insight problems. These findings suggest that physiological response to problem‐solving is dependent on the type of problem and the amount of challenge it poses to an individual.